Radiographic and histomorphometric analysis of bone healing using autogenous graft associated with platelet-rich plasma obtained by 2 different methods - Hatakeyama, Marcia; Beletti, Marcelo E.; Zanetta-Barbosa, Darceny [UNESP]; Dechichi, Paula (Mosby-elsevier, 2008)
The aim of this study was to conduct radiographic and histomorphometric analysis of bone healing in the calvaria of rabbits, using an autogenous graft associated with PRP obtained by 2 different methods. Thirty rabbits were divided into control and experimental groups. Lesions were produced in the calvaria and filled with autogenous graft ( control) or autogenous graft and PRP obtained by the Anitua or modified Sonnleitner methods. The animals were humanely killed 15 days after surgery and the calvarias were radiographed. The radiographs were digitized to assess the radiographic density. By histologic images of the lesion, the bone matrix was quantified. There were no significant differences in the radiographic density and the bone matrix area between the groups. The association of PRP with autogenous bone did not improve the healing process, irrespective of the method used early during healing.